PAULUS RASUL BANGSA-BANGSA - Mahulae, Kristinus C (UNIKA Santo Thomas, 2008)
Our Pope Benedict XVI has decided that from June 2008 to June 2009 as the Year of St Paul. This occasion would be a very good time for us every catholic to study the life of the Apostle Paul, to see what he has done, and if its possible to compare our life with him.Paul was keenly aware of himself as a Jew and boasted of his Jewish background (Rom 11:1; Phil 3:5; 2 Cor 11:22). He was educated at the feet of Gamaliel (Acts 22:3). In the experience near to Damascus, by the revelation of the Son by the Father (Gal 1:16), the crucified Lord of glory (1 Cor 2:8) summoned Paul the Pharisee to become an apostle. Paul spoke of his call as an event in which he had been seized by Christ Jesus (Phil 3:12) for preaching the Gospel to Gentiles (1 Cor 9:16; Gal 1:16). His response to that call was his vivid faith in Christ Jesus. He had journey for (“from Jerusalem all the way around to Illyricum” Rom 15:19) and laboured hard to become not only ‘the apostle of the Gentiles” (Rom 11:13), but an “ambassador for Christ Jesus” (2 Cor 5:20).